Antioxidant vitamins in the context of nonalcoholic fatty liver disease in obese children and adolescents - Fábio da Veiga Ued; Virgínia Resende S. Weffort (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To review the literature on the importance of antioxidant vitamins, analyzed in the context of dietary intake, its plasma levels, and its current use as a supplementation treatment in obese children and adolescents with nonalcoholic fatty liver disease. DATA SOURCES: The articles were identified in Lilacs, Ibecs, SciELO, PubMed/Medline, and Scopus databases. To conduct the survey, the "fatty liver" descriptor was associated to the following words: "children", "antioxidants" and "vitamins". The search was limited to articles written in Portuguese, Spanish and English, with publication date until December, 2012. DATA SYNTHESIS: Six studies were selected. The survey revealed a low dietary intake and low antioxidant vitamins serum levels in this population. The changes in lifestyle, with adequate dietary intake of vitamins, and the increase in physical activity were associated with a significant improvement in liver histology and in laboratory tests. Vitamin supplementation also improved the disease progression markers, as the alanine aminotransferase serum levels and the histological characteristics of lobular inflammation and hepatocellular damage. However, these improvements were not statistically significant in all studies. CONCLUSIONS: There is insufficient evidence to recommend or to refute antioxidant supplementation in patients with simple steatosis or steatohepatitis. The changes in lifestyle seem to be, at the present time, the more advisable therapy.